Anesthetic management of robot-assisted thoracoscopic thymectomy - Anil Karlekar; Devesh Dutta; Ravindra Saxena; Krishna Kant Sharma (Journal of Anaesthesiology Clinical Pharmacology, 2016)
Myasthenia gravis (MG) is a rare disorder involving neuromuscular junction. In conjunction with medical therapy, thymectomy is a known modality of treatment of MG and has shown to increase the probability of remission and overall symptomatic improvement. For minimally invasive thymectomy, video-.assisted thoracoscopic surgery has been the preferred surgical approach till recently. The robotic surgical procedure must necessarily bring new challenges to the anesthesiologists to effectively meet the specific requirements of the technique. At present, there is a paucity of literature regarding the anesthetic concerns of robotic assisted thymectomy, patient in question specifically posed a challenge since different maneuvers and techniques had to be tried to obtain optimum surgical conditions with stable ventilatory and hemodynamic parameters. Concerns of patient positioning and hemodynamic monitoring have also been discussed.